Development and initial validation of the bronchiectasis exacerbation and symptom tool (BEST) - Artaraz, Amaia (Respir Res, 2020)
BACKGROUND: Recurrent bronchiectasis exacerbations are related to deterioration of lung function, progression of the disease, impairment of quality of life, and to an increased mortality. Improved detection of exacerbations has been accomplished in chronic obstructive pulmonary disease through the use of patient completed diaries. These tools may enhance exacerbation reporting and identification. The aim of this study was to develop a novel symptom diary for bronchiectasis symptom burden and detection of exacerbations, named the BEST diary. METHODS: Prospective observational study of patients with bronchiectasis conducted at Ninewells Hospital, Dundee. We included patients with confirmed bronchiectasis by computed tomography, who were symptomatic and had at least 1 documented exacerbation of bronchiectasis in the previous 12 months to participate. Symptoms were recorded daily in a diary incorporating cough, sputum volume, sputum colour, dyspnoea, fatigue and systemic disturbance scored from 0 to 26. RESULTS: Twenty-one patients were included in the study. We identified 29 reported (treated exacerbations) and 23 unreported (untreated) exacerbations over 6-month follow-up. The BEST diary score showed a good correlation with the established and validated questionnaires and measures of health status (COPD Assessment Test, r = 0.61, p = 0.0037, Leicester Cough Questionnaire, r = − 0.52,p = 0.0015, St Georges Respiratory Questionnaire, r = 0.61,p < 0.0001 and 6 min walk test, r = − 0.46,p = 0.037). The mean BEST score at baseline was 7.1 points (SD 2.2). The peak symptom score during exacerbation was a mean of 16.4 (3.1), and the change from baseline to exacerbation was a mean of 9.1 points (SD 2.5). Mean duration of exacerbations based on time for a return to baseline symptoms was 15.3 days (SD 5.7). A minimum clinically important difference of 4 points is proposed. CONCLUSIONS: The BEST symptom diary has shown concurrent validity with current health questionnaires and is responsive at onset and recovery from exacerbation. The BEST diary may be useful to detect and characterise exacerbations in bronchiectasis clinical trials.